Can dialogues around girls' education improve academic outcomes? Evidence from a randomized development project - Christopher Cotton; Ardyn Nordstrom; Jordan Nanowski; Eric Richert (Queen's University, Department of Economics, 2022)
We evaluate the impact of deliberative dialogues about girls' education with groups of parents, teachers, and girls on the education outcomes of girls in rural Zimbabwe. Dialog-based engagement campaigns increased mathematics performance and school enrolment. In later periods, the program was expanded to provide resources and an updated curriculum. During these later periods, we observed improvements in literacy, but no additional improvements in mathematics and enrolment beyond what was observed following the dialog-based engagement campaign alone. A mediation analysis shows how earlier gains in math performance due to the dialogues are positively associated with later gains in literacy.
Keywords: I24; I25; J16; O12; O15; 330; Girls' Education Challenge; education; impact evaluation; randomized controlled trial; multifaceted intervention; community conversations; deliberate dialogues; social norms